Blind Spot Detection to Prevent Serious Accidents for Children in Cyclists - Utari Sanaba; Virhan Mujahid Syufie; Rasyeedah Binti Mohd Othman; Muhammad Richard Dzaki Dharma (Department of Electrical Engineering Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Bicycles are a mode of transportation used not only to move a person from one point to another but also commonly as a means of exercise. The lack of a safety system on bicycles increases the risk of accidents and theft, especially for children who have not yet developed stable emotional control while cycling. The use of ultrasonic sensors can be applied as detectors to provide early warnings when a cyclist is about to switch lanes, considering the wide blind spot area for cyclists. In this research, the system includes an application that can control a smart lock and the boundaries of the detector using the TCP/IP protocol via SIM900A, allowing the bicycle owner to manage the device's condition and monitor the bicycle's location. After going through several stages of testing and analyzing the results, it can be concluded that the transmission of GPS position data was successfully stored and accurately reflected in the database, with errors of 0.0012614% and 5.41295E-05% for latitude and longitude data, respectively. The blind spot detector successfully measured the distance of walls and motor vehicles located within the cyclist's blind spot area with an accuracy of 85.54%, and the safety system—comprising the lock and LED indicator—was also successfully activated when a vehicle approached the cyclist within the blind zone.